Perancangan Dan Pengembangan E-Catalog Andra Laundry - Jimmy Pratama; Jacky Christhomas (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This community service program has the aim of increasing sales, reaching a wider sales market and adding new consumers by using social media. Partners in community service are the Andra Laundry Shop which is a shop engaged in laundry services located at Jalan Sungai Maham No. 118, Singkawang, West Kalimantan. The method used in this activity is observation, interviews and implementation on social media. The implementation results show an increase in new marketing reach, an increase in turnover and an increase in new consumers